Reactive oxygen species induce MMP12-dependent degradation of collagen 5 and fibronectin to promote the motility of human umbilical cord-derived mesenchymal stem cells - Yun, Seung Pil (Blackwell Publishing Ltd, 2014)
BACKGROUND AND PURPOSE: Reactive oxygen species (ROS) are potent regulators of stem cell behaviour; however, their physiological significance as regards MMP-mediated regulation of the motility of human umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) has not been characterized. In the present study, we investigated the role of hydrogen peroxide (H(2)O(2)) and associated signalling pathways in promoting UCB-MSCs motility. EXPERIMENTAL APPROACH: The regulatory effects of H(2)O(2) on the activation of PKC, MAPKs, NF-κB and β-catenin were determined. The expressions of MMP and extracellular matrix proteins were examined. Pharmacological inhibitors and gene-specific siRNA were used to identify the signalling pathways of H(2)O(2) that affect UCB-MSCs motility. An experimental skin wound-healing model was used to confirm the functional role of UCB-MSCs treated with H(2)O(2) in ICR mice. KEY RESULTS: H(2)O(2) increased the motility of UCB-MSCs by activating PKCα via a calcium influx mechanism. H(2)O(2) activated ERK and p38 MAPK, which are responsible for the distinct activation of transcription factors NF-κB and β-catenin. UCB-MSCs expressed eight MMP genes, but only MMP12 expression was uniquely regulated by NF-κB and β-catenin activation. H(2)O(2) increased the MMP12-dependent degradation of collagen 5 (COL-5) and fibronectin (FN) associated with UCB-MSCs motility. Finally, topical transplantation of UCB-MSCs treated with H(2)O(2) enhanced skin wound healing in mice. CONCLUSIONS AND IMPLICATIONS: H(2)O(2) stimulated UCB-MSCs motility by increasing MMP12-dependent degradation of COL-5 and FN through the activation of NF-κB and glycogen synthase kinase-3β/β-catenin, which is critical for providing a suitable microenvironment for MSCs transplantation and re-epithelialization of skin wounds in mice.